Do changes in tax regulation affect firms’ capital structure? - Arrója, Gonçalo Maria Tender Sacadura (2017)
The aim of this dissertation is to assess how changing tax regulation may affect the capital structure of firms, in particular, how the introduction of a new tax provision – the Notional Interest Deduction (NID) – impacted firms’ financing decisions in Italy. To perform this study, we gathered company data from 2005 to 2015 and we analysed a sample of 197 Italian public firms, separating them into two distinct groups: (i) Financial companies and (ii) Nonfinancial companies. While for Financial companies it seems that the NID implementation did not translate itself into statistically significant effects, results show that for Non-financial companies there is a slightly increase of 2% in leverage ratios, that is softened for more profitable firms. Results seem to be robust when changing the form of treatment regarding outliers and also when altering the time period of our analysis.